Patient Data Privacy Challenges in Electronic Health Systems: A Juridical Analysis of Medical Information Protection in Indonesia - Santhi, Ni Nyoman Putri Purnama (West Science Law and Human Rights, 2025)
The digital revolution has fundamentally transformed healthcare service systems, bringing complex legal issues related to patient data privacy protection. This research aims to analyze the juridical challenges of electronic medical information protection in Indonesia. Using a normative juridical method, the research examines regulatory frameworks, identifies legal gaps, and formulates responsive legal protection models. Research findings reveal that Indonesia's electronic health systems face structural weaknesses in guaranteeing data privacy. Existing regulations have not been able to accommodate digital technology developments, creating risks of medical information leakage and misuse. The complexity of challenges includes weak digital consent mechanisms, absence of cybersecurity standards, and minimal supervision. The research recommends comprehensive regulatory framework renewal, establishment of independent oversight bodies, and development of adaptive health data security protocols. This transformation requires an interdisciplinary approach that integrates legal, technological, and ethical perspectives. The research conclusion emphasizes the urgency of patient privacy rights protection in digital ecosystems while ensuring the effectiveness of modern healthcare services.